RANCANG BANGUN SISTEM PEMANTAU DAN TRANSMISI DATA TEKANAN DARAH PADA MOBILE PLATFORM ANDROID MENGGUNAKAN KONEKSI BLUETOOTH - Nainggolan, Parlindungan Fernando; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems, 2015)
Blood pressure measuring device is one of the tools people use to measure blood pressure. Therefore, many of the technologies used to develop a blood pressure measuring device. This study has been designed a blood pressure data transmission on android using a Bluetooth connection. The blood pressure measuring device can measure blood pressure using a pressure sensor MPX 5100DP. Then the data is processed by microcontroller and displayed on the LCD and also on android by the bluetooth connection with HC-05. In this study obtained average systolic measurement error is equal to 3.687% and the average diastolic measurement error is equal to 4.768%.